Website for scientific dissemination of research on problem-based learning with highschool chemistry teachers: Contexts of an investigation (Research, Society and Development, 2021)
The aim of this study was to carry out the scientific dissemination of research on problem-based learning (PBL) with highschool Chemistry teachers through a website and to investigate their opinions on this digital resource. Also, analyse the knowledge of teachers about PBL and its use in the classroom. The set of data was collected through of a semi-structured interview  conducted with ten highschool Chemistry teachers in the city of Recife - Pernambuco, Brazil. Analysis of data implied that teachers know PBL and that they use it in the classroom, however with some difficulties. In general, their opinions about the website were positive and significant. Most of them commented that the website will serve as a didactic support in the preparation of their lessons providing access to solutions to various problematic situations regarding different contents in chemistry. Furthermore, the website will allow basic education teachers to have access to knowledge that has been discussed in Brazilian universities.